Look! what do you see? an art puzzle book of American & Chinese songs - Xu, Bing 1955- (Viking, Penguin Young Readers, 2017)
"Seventeen traditional American and Chinese songs are written in artist Xu Bing's signature Square Word Calligraphy"...